MHCAF-Net: Multi-Scale Cross-Attention Fusion for Histological Grading of Invasive Ductal Carcinoma - Cella, Mario Vitor Vieira; Oliveira, Alejandro Costa de; Soares Filho, Celso Luiz Silva; Quintanilha, Darlan Bruno Pontes; Borchartt, Tiago Bonini; Clímaco, Francisco Glaubos Nunes; Almeida, João Dallyson Sousa de Almeida (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais do XXVI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2026.21032, 2026)
Breast cancer remains a critical global health challenge, requiring precise diagnostic tools for effective treatment planning. While mammography is the standard screening tool, histopathological analysis remains the gold standard for confirming diagnoses and detailing tissue characteristics. However, determining the histological grade of Invasive Ductal Carcinoma (IDC) presents significant morphological ambiguity, where global tissue structures often contradict local cellular details. This work introduces a architecture using Convolutional Neural Networks (CNNs) to classify the histological grade of IDC. The primary contribution resides in an attention-based fusion mechanism that integrates multi-scale representations of histopathological images. The approach achieved results of 85.29%±3.0% accuracy, 85.22%±2.9% F1-Score, 89.56%±2.7% precision, and 81.36%±4.2% recall. These results demonstrate the viability of the proposed approach, which effectively captures both tissue architecture and cellular morphology to assist pathologists in accurate medical image analysis.